Molecular Biology and Pathogenesis of Peste des Petits Ruminants Virus - Munir, Muhammad. (SpringerBriefs in Animal Sciences, 2013)
Peste de Petits Ruminants (PPR) is a highly contagious viral disease of domestic and wild small ruminants that can significantly affect economies. The authors are experts in the field and provide an up-to-date and comprehensive review covering all aspects of the disease. The book is divided into seven chapters highlighting genome organization, virus replication and the determinants of virulence, pathophysiology and clinical disease, immunology and immunopathogenesis, epidemiology, diagnostic assays and vaccines, and the challenges concerning global eradication. It is an invaluable reference work, presenting the latest information for virologists, microbiologists, immunologists, veterinarians, and scientists working in PPR research.